Pengaruh Profesionalisme Auditor Terhadap Pertimbangan Tingkat Materialitas Dalam Proses Pengauditan Laporan Keuangan (Studi Kasus Pada Auditor Kap Di Yogyakarta Dan Semarang) - Kusumadika, Riky Seftian; , Wahyono, Drs, Ak, MA (2016)
This study aimed to examine the effect of professionalism in five dimensions: dedication to the profession, social responsibility, independence, confidence in the profession and relationships with colleagues on the level of materiality considerations in the examination of financial statements. This study used convenience sampling method is sampling techniques freely. The number of samples collected as many as 35 pieces of 4 public accounting firm in Yogyakarta and 3 public accounting firm in Semarang. The data collected was analyzed using test data quality and classical assumption. Testing the hypothesis in this study using multiple linear regression analysis with t-test, f and the coefficient of determination. The results of this study evidenced by thitung> ttable namely dedication (3,353>2,045), social obligations (2,170>2,045), independence (-3.599>-2,045), confidence in the profession (2,190>2,045), relationship with colleagues (2.302>2045) with a significance value of 0.05. So all the variables studied had an influence on the level of materiality considerations in the examination of financial statements. Keywords: Dedication to the Profession, Social Responsibility, Independence, Confidence In the Profession, Relationships with colleagues